2013
DOI: 10.1371/journal.pone.0063180
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sodium in the RprY-Dependent Stress Response in Porphyromonas gingivalis

Abstract: Porphyromonas gingivalis is a Gram-negative oral anaerobe which is strongly associated with periodontal disease. Environmental changes in the gingival sulcus trigger the growth of P. gingivalis and a concurrent shift from periodontal health to disease. Bacteria adjust their physiology in response to environmental changes and gene regulation by two-component phospho-relay systems is one mechanism by which such adjustments are effected. In P. gingivalis RprY is an orphan response regulator and previously we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 43 publications
1
24
0
Order By: Relevance
“…Strains of Escherichia coli were derivatives of K12 that were grown in Luria Bertani broth or plates at 37°C, and when appropriate with the addition of antibiotics (ampicillin 100 μg/ml or kanamycin 50 μg/ml). Cultures of P. gingivalis strain ATCC 33277 were grown in tryptic soy broth (TSB) as described previously [3] with erythromycin (5 μg/ml) or tetracycline (2 μg/ml) when appropriate. Cultures were grown in an anaerobic chamber (Coy) in an atmosphere of 85% nitrogen, 5% hydrogen, and 10% carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Strains of Escherichia coli were derivatives of K12 that were grown in Luria Bertani broth or plates at 37°C, and when appropriate with the addition of antibiotics (ampicillin 100 μg/ml or kanamycin 50 μg/ml). Cultures of P. gingivalis strain ATCC 33277 were grown in tryptic soy broth (TSB) as described previously [3] with erythromycin (5 μg/ml) or tetracycline (2 μg/ml) when appropriate. Cultures were grown in an anaerobic chamber (Coy) in an atmosphere of 85% nitrogen, 5% hydrogen, and 10% carbon dioxide.…”
Section: Methodsmentioning
confidence: 99%
“…DNA primers were synthesized by integrated DNA Technologies. The rprY (PGN_1185) deletion strain of ATCC 33277 was constructed as described earlier [3]. Briefly, using three-way SOEing (splicing by overlap extension) [7], PCR amplicons containing sequences 1054 bp upstream and 1047 bp downstream of the PGN_1185 ORF were ligated to an ErmF-ErmAM cassette.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of sodium (Na + ) depletion as a potential environmental signal to activate RprY function was further investigated [46]. In Escherichia coli , an RprY–LacZ fusion protein was induced specifically by Na + depletion; however, P. gingivalis rprY and oxyR mutants were unable to grow in a similar medium.…”
Section: Rr Rprymentioning
confidence: 99%
“…Taken together, these results suggest that RprY may be a constitutively expressed repressor and that, in the absence of a cognate HK, its function is modulated by the acetylation activity of Pat. The exact role of Na + depletion on expression of RprY is still unknown, although the rprY mutant has the same growth phenotype as an oxyR mutant during depletion, suggesting a role in the oxidative stress response [46]. Interestingly, it was recently demonstrated that the NQR pump of V. cholerae is a generator of ROS, specifically associated with reduced a flavin adenine dinucleotide cofactor of subunit F ( nqrF ) of the complex [45].…”
Section: Rr Rprymentioning
confidence: 99%